Health Belief as a Determining Factor in the Behavior of Complementary Therapy use in Cancer Patients Undergoing Treatment - Werdani, Yesiana Dwi Wahyu; Sari, Nia Novita (STIKep PPNI Jawa Barat, 2025)
Aims: Analyzing the correlation between health beliefs and the behavior of using complementary therapies in cancer patients. Methods: The study was conducted at the Indonesian Cancer Foundation (YKI) East Java Branch, Surabaya in July 2024 using a correlation design and cross-sectional approach and added interview methods to support quantitative data results. The population of all cancer patients at YKI, 33 patients was obtained according to the inclusion criteria. The instruments used were the Health Belief Questionnaire, and the Scale for Attitudes Towards Complementary and Alternative Medicine (SACAM), and continued by in deep interview to support the quantitative data. Results: Mean of health belief score was 77.88 + 11.467 (good health belief category), and mean of the behavior of using complementary therapies was 42.48 + 8.758 (neutral behavior category). The results of the Kendal Tau test (p < 0.05) showed a significant correlation between health beliefs and behavior of using complementary therapies (p-value = 0.000). Conclusions: Health beliefs are an important factor for cancer survivors in determining their decision-making behavior regarding medical treatment and complementary treatments.